The Price of Peace Just War in the Twenty-First Century - Reed, Charles (Cambridge University Press, 2013)
The genesis of this book lies in a March 2005 symposium on the ‘JustWar in the Twenty-First Century’ and the context for the encounter was the 2003 Iraq War, a conflict that helped to crystallise in the most acute way the recurring moral, political, legal and military tensions that are involved in the recourse to and conduct of war. Historically, the framework used most frequently to explore these issues has been the just war tradition1 and the symposium aimed to facilitate a transatlantic dialogue involving a diverse range of participants on the ethics of war and peace with a view to investigating and renewing that tradition as part of a broader public conversation.